PLEKHS1: A new molecular marker predicting risk of progression of non-muscle-invasive bladder cancer - Pignot, Géraldine (Oncol Lett, 2019)
Promoter mutations of pleckstrin homology domain-containing S1 (PLEKHS1) are frequent in several cancer types. To evaluate the DNA mutations, the mRNA expression and prognostic value of PLEKHS1 was evaluated in bladder cancer. We investigated DNA mutations and mRNA expression of PLEKHS1 in a first series of 154 bladder tumors [71 non-muscle-invasive bladder cancer (NMIBC) and 83 muscle-invasive bladder cancers (MIBC)] from patients who underwent transurethral bladder resection or radical cystectomy between 2001 and 2006, and 20 normal bladder samples. Results were then validated in a second series of 181 bladder tumors (91 NMIBC and 90 MIBC). All patients have signed an informed consent form. DNA mutations were analysed by high-resolution melt analysis and sanger sequencing. The mRNA expression was measured by real-time reverse-transcriptase quantitative PCR. The results of the molecular analysis were compared with survival data. PLEKHS1 mutations occurred in 25.0 and 32.2% of NMIBC and MIBC, respectively in the first series. These results were confirmed in the second series (33.0 and 37.8% of NMIBC and MIBC, respectively). In MIBC, DNA mutations were significantly more frequent with the basal than non-basal phenotype (61.5 vs. 27.1%; P=0.0025). The PLEKHS1 mRNA level was increased in 22.5 and 27.7% of NMIBC and MIBC tumors but was not associated with DNA mutations. In NMIBC, PLEKHS1 mRNA overexpression was significantly associated with progression to muscle-invasive disease (P=0.0069) and remained an independent prognostic factor on multivariate analysis (P=0.034). DNA mutations of PLEKHS1 occurred in one-third of bladder tumors and was frequent in the basal MIBC phenotype. PLEKHS1 mRNA overexpression may be an independent prognostic factor of progression-free survival in NMIBC.